Predictors of mosaic chromosome Y loss and associations with mortality in the UK Biobank - Loftfield, Erikka (Sci Rep, 2018)
Mosaic loss of the Y chromosome (mLOY) is the most commonly reported large structural somatic event. Previous studies have indicated age and cigarette smoking increase the risk of mLOY, but the relationship of other exposures with mLOY and mLOY with disease has not been adequately investigated. We characterized mLOY in a large cohort of 223,338 men from the UK Biobank by scanning for deviations in genotyping array median log(2) intensity ratios (mLRR) of the Y chromosome using a standard algorithm. A total of 3,789 (1.7%) men showed evidence for mLOY (mLRR < −0.15). In multivariable-adjusted logistic regression models, we found that mLOY increases exponentially with age (overall P-value < 4.9 × 10(−324); p-value for the quadratic term = 2.1 × 10(−7)), and observed a strong association with current smoking (P-value = 7.8 × 10(−184)). We observed less mLOY in men of African ancestry (0.4%) compared to men of European ancestry (1.8%, P-value = 0.003). Although mLOY was not associated with prevalent cancer (P-value = 0.61), associations were observed for diabetes (P-value = 0.003) and cardiovascular disease (P-value = 0.01). Using Cox proportional hazards regression models, mLOY was associated with all-cause mortality among men with a high proportion of cells affected (mLRR < −0.40; HR = 1.35, 95% CI = 1.08–1.70, P-value = 0.009). In conclusion, mLOY was associated with several health-related factors as well as with all-cause mortality. Further functional studies are warranted to understand how and in what way mLOY could influence adult male health.